The Effect of Spiritual Gratitude and Religious Coping Levels on Psychological Resilience in Earthquake Survivor Students 1 Year After the Earthquake in Türkiye - Gümüş Şekerci, Yasemin (Journal of religion and health, 2025)
Cultural factors are effective in the emergence of psychological resilience. This study aims to determine the psychological resilience, spiritual gratitude, and religious coping levels of students who experienced the Kahramanmaraş earthquake 1 year after the earthquake, and to examine the effect of spiritual gratitude and religious coping levels on the level of psychological resilience. This is a descriptive and correlational study. A total of 176 Emergency Relief and Disaster Management students who experienced the Kahramanmaraş earthquake in Türkiye were included in the study. Data were collected using the Personal Information Form, Brief Psychological Resilience Scale, Spiritual Gratitude Scale, and Religious Coping Scale. Statistical evaluations were made using descriptive analyses as well as Independent Sample t-test, One-way ANOVA, Pearson's correlation, and multiple linear regression analysis. Psychological resilience was positively associated with spiritual gratitude and positive religious coping levels (p < .05). The findings showed that 1 year after the earthquake, spiritual gratitude and religious coping levels of earthquake survivor students were associated with psychological resilience.